Cross-Border Health Care Services as Inward Internationalization - Cotta de Mello, Renato; da Rocha, Angela; Pacheco, Henrique F. (Internext, 2021)
Purpose: The research aimed at investigating the pre-conditions and the decision-making process by which physician-entrepreneurs adopt CBHCS as part of their business. Method: The study uses the case method of investigation. Main results: Results showed that, in the cases studied, international experience and international networking are relevant characteristics of the physician-entrepreneur, besides country reputation, cultural and language similarities, and physician reputation. In addition, the decision processes of the physician-entrepreneurs in these organizations are based on an effectual logic. The offer of cross-border health care services was a combination of given means and contingencies, which helped the entrepreneurs to discover, or to create, the opportunity, and then develop it. Relevance/originality: The research combines the literatures on effectuation and inward internationalization to study the decision-making process of adopting CBHCS by medical clinics. Theoretical contributions: The study contributes to the literature by identifying certain pre-conditions and providing an in-depth analysis of the use of effectual logic by physician-entrepreneurs in their decision-making process of adopting CBHCS.